An unfinished love story : a personal history of the 1960s [large type] - Goodwin, Doris Kearns (Thorndike Press large print nonfiction series., 2024)
"Dick and Doris Goodwin were married for forty-two years and married to American history even longer. Dick was one of the young men of John F. Kennedy's New Frontier, and he both named and helped design Lyndon Johnson's Great Society. Doris was a White House Fellow and worked directly for Lyndon Johnson, later assisting on his memoir. The Goodwins' last great adventure involved opening the more than three hundred boxes of letters, diaries, documents and memorabilia Dick had saved for more than fifty years. The voyage of remembrance revived the hope that the youth of today will carry forward this love story with America"--